SIGN CHARACTER OF THE EXPONENTS OF MODALITY IN A LEGAL TEXT - LIZISOWA, Maria Teresa (Comparative Legilinguistics, 2017)
The thesis of this article is that the texts of legislative acts represent the most natural speech. Legal language becomes complete in depicting the world as well as in expressing the will of a legislator and his attitude to what is said by him, both on deictic and symbolic level. Informality in legal language is a desired feature – working on the assumption that an ordinary ethnic language is correctly interpreted.